Implementing peer recovery services for overdose prevention in Rhode Island: An examination of two outreach-based approaches. (February 2019) - Waye, Katherine M.; Goyer, Jonathan; Dettor, Debra; Mahoney, Linda; Samuels, Elizabeth A.; Yedinak, Jesse L.; Marshall, Brandon D.L.
Abstract: Background: Rhode Island has the tenth highest rate of accidental drug overdose deaths in the United States. In response to this crisis, Anchor Recovery Center, a community-based peer recovery program, developed programs deploying certified Peer Recovery Specialists to emergency departments (AnchorED) and communities with high rates of accidental opioid overdoses (AnchorMORE). Objectives: The purpose of this paper is to describe AnchorED and AnchorMORE's activities and implementation process. Methods: AnchorED data were analyzed from a standard enrollment questionnaire that includes participant contact information, demographics, and a needs assessment. The AnchorED program outcomes include number of clients enrolled, number of naloxone training sessions, and number of referrals to recovery and treatment services. Overdose deaths and naloxone distribution through AnchorMORE were mapped using Tableau software. Results: From July 2016–June 2017, AnchorED had 1329 contacts with patients visiting an emergency department for reported substance misuse cases or suspected overdose. Among the contacts, 88.7% received naloxone training and 86.8% agreed to continued outreach with a Peer Recovery Specialist after their ED discharge. Of those receiving peer recovery services from the Anchor Recovery Community Center, 44.7% ( n  = 1055/2362) were referred from an AnchorED contact. From July 2016–June 2017, AnchorMORE distributed 854 naloxone kits in high-risk communities and provided 1311 service referrals. Conclusion: These findings indicate the potential impact peer recovery programs may have on engaging high-risk populations in treatment, overdose prevention, and other harm reduction activities. Additional research is needed to evaluate the reach of implementation and services uptake. Highlights: Peer Recovery Specialists are part of the overdose response in Rhode Island Specialists provide overdose outreach to emergency departments (ED) and communities From July 2016-June 2017, ED-based Peer Recovery Specialists had 1329 contacts Of the ED contacts, 89% had naloxone training and 87% agreed to specialist engagement post-ED In communities, specialists gave 854 naloxone kits from July 2016-June 2017